Demographic determinants of self-medication in the population covered by health centers in Tabriz - Hamid Reza Shaamekhi; Mohammad Asghari Jafarabadi; Mahasti Alizadeh (Tabriz University of Medical Sciences, 2019)
Background: Self-medication is the choice and use of medications by people to treat a self diagnosed illness or symptom. The aim of this study was to search the relationship between a number of socio-demographic conditions and self-medication in the population covered by health complexes in Tabriz, Iran. Methods: This study was a cross-sectional descriptive-analytic study and was carried out on the population covered by health complexes in Tabriz. Participants were recruited by a multi-stage sampling method. A total of 1000 participants were included in the study. Data collection was done using a researcher-created questionnaire. Data were analyzed using chi-square test and logistic regression. Results: The incidence of self-medication was 70.9% for participants who reported illness in the last month. The chance of self-medication was higher in young (P=0.007) and middleaged (P=0.012) groups, and housewives (P=0.048); and was lower among participants who were not literate (P=0.047). There was no significant relationship between gender and self medication (P=0.553). The high cost of visits was mentioned as a reason for self-medication. The most frequently mentioned drugs used in self-medication were analgesics, cold medicines, and antibiotics, respectively. More frequent reasons for self-medication were the previous experience of the disease, the assumption that the ailment was not important, and the high cost of visits, respectively. Conclusion: The prevalence of self-medication in this study was high. Considering the results, education in the community, financial support, and monitoring the delivery of drugs can play an important role in improving the pattern of drug use.